GEODETIC OBSERVATIONS OF ICE FLOW VELOCITIES OVER THE SOUTHERN PART OF SUBGLACIAL LAKE VOSTOK, ANTARCTICA, AND THEIR GLACIOLOGICAL IMPLICATIONS - Wendt J.; Dietrich R.; Fritsche M.; Wendt A.; Yuskevich A.; Kokhanov A.; Senatorov A.; Lukin V.; Shibuya K.; Doi K. (My University, 2006)
In the austral summer seasons 2001/02 and 2002/03, Global Positioning System (GPS) data were collected in the vicinity of Vostok Station to determine ice flow velocities over Lake Vostok. Ten GPS sites are located within a radius of 30km around Vostok Station on floating ice as well as on grounded ice to the east and to the west of the lake. Additionally, a local deformation network around the ice core drilling site 5G-1 was installed. The derived ice flow velocity for Vostok Station is 2.00ma-1 ± 0.01ma-1. Along the flowline of Vostok Station an extension rate of about 10 -5 a-1 (equivalent to 1cm km-1a-1) was determined. This significant velocity gradient results in a new estimate of 28 700 years for the transit time of an ice particle along the Vostok flowline from the bedrock ridge in the southwest of the lake to the eastern shoreline. With these lower velocities compared to earlier studies and, hence, larger transit times the basal accretion rate is estimated to be 4mm a-1 along a portion of the Vostok flowline. An assessment of the local accretion rate at Vostok Station using the observed geodetic quantities yields an accretion rate in the same order of magnitude. Furthermore, the comparison of our geodetic observations with results inferred from ice-penetrating radar data indicates that the ice flow may not have changed significantly for several thousand years. © 2006 The Authors Journal compilation © 2006 RAS.
Keywords: ANTARCTICA; GEODESY; GLACIOLOGY; GPS; ICE FLOW VELOCITY; LAKE VOSTOK